Democracies challenges to societal health - Wejnert, Barbara (Bingley, U.K. : Emerald, 2011)
Volume 19 in the Research in Political Sociology series is devoted to health problems, challenges and accomplishments in democratic societies. It includes papers addressing health systems, health policies, obstacles to societal healthy behaviors, and/or health conditions that are experienced in democratic societies in the world. The democratic society is understood in a broadly defined term. It includes developed Western democracies, as well as less developed or underdeveloped countries that have democratic system. According to such definition, the category 'democracies' includes democratic countries that have well established democratic system and respect broad network of people rights, as well as democracies that are formally consider democratic states but de facto respect only a few rights or their governments are guided by limited democratic principles. Therefore, the collection of the 19th volume of Research in Political Sociology includes papers addressing these issues in a broad spectrum of countries from India, Sri Lanka and Tanzania, to Sweden, Canada and the United States.
Issues in health, democracy, and development / Barbara Wejnert -- Human rights and health status of girls and young women in Afghanistan under the new democracy : forced and child marriages / Andrea Parrot -- School health : a way to the future? / Eunice Rodriguez, Diana Austria, Melinda Landau -- Health, development, and democracy : health systems in Southeast Asia and in Eastern Europe / Nirupama Prakash, Barbara Wejnert -- Transformation of health services in Poland since 1989 democratization / Elzbieta Sawa-Czajka -- The nutrition and health of women and children in the aftermath of natural disasters / Sitora Khakimova -- Domestic violence against women in rural Rajasthan, India : a sociological analysis / Nirupama Prakash -- Women and domestic violence : a case study in rural Sri Lanka / Seeta Aladuwaka, Ram Alagan -- Natural disaster, gender, and challenges : lessons from Asian tsunami / Ram Alagan, Seela Aladuwaka -- The declining health status as fuelled by illusory internal migration in sub-Saharan Africa : is there any future? / Rasel Madaha, Barbara Wejnert -- Health, gender, and democracy in Nepal / Shiba S. Banskota -- Global development, populations' health, and democracy : policy recommendations / Barbara Wejnert.
Keywords: Political Science -- Political Ideologies / Democracy; Medical -- Health Policy; Political structures: democracy; Politics & government; Political sociology; Democracy